Sekolah Alam Bogor (SAB): Strategi Menginternalisasi Nilai-nilai Akhlak Melalui Pembelajaran Tematik - Didin Saepudin; Robiah Ummi Kulsum (JURNAL INDO-ISLAMIKA, 2019)
This article describes a discourse that an educational school is to play a role as a door for its students to solve their life problems. This paper argues that a good school will organize itself with a management system that supports this role. This paper uncovers that Sekolah Alam Bogor (SAB/an Outdoor School in Bogor, West Java) implements this management. Consequently, this school qualifies its students with a competence to develop themselves.